DEVELOPMENT OF QR CODE TECHNOLOGY FOOD ORDERING APP FOR LIMESTONES BALI RESTAURANT WITH USER CENTERED DESIGN AND USABILITY TESTING - Anak Agung Adi Wiryya Putra; I Gusti Ayu Agung Istri Dinda Larasshanti Jelantik; Komang Agus Putra Kardiyasa; Kadek Adyatna Wedananta; I Gusti Ngurah Agung Dava Danendra (Computer Science Department, Malang National Institute of Technology, 2026)
While digital adoption is essential for operational efficiency in the culinary sector, many local restaurants still struggle with the inefficiencies of manual ordering and paper menus, which require longer service times and complicate menu updates. Currently, there is a gap in applying structured, user-focused methodologies to effectively bridge these traditional practices with modern digital solutions. To address this gap, this research aims to design a highly usable UI/UX for a web-based QR Code food ordering system tailored specifically for Limestones Restaurant Bali. The study utilizes the User-Centered Design (UCD) method to ensure the system strictly aligns with user needs, progressing through four stages: specifying the context of use, specifying user and organizational requirements, producing design solutions, and evaluating the design against user requirements. The resulting prototype features an interactive digital menu, shopping cart, and two payment options including QRIS and cash. Design evaluation was conducted through user testing with ten respondents using the System Usability Scale (SUS), achieving a score of 71.25. This score places the system in the